Root growth and cotton nutrition as affected by liming and soil compaction - Rosolem, Ciro Antonio [UNESP]; Schiochet, M. A.; Souza, L. S.; Whitacker, JPT (Taylor & Francis Inc, 1998)
Soil columns were produced by filling PVC tubes with a Dark Red Latosol (Acrortox, 22% of clay). A compacted layer was established at the depth of 15 cm in the columns. In the compacted layer, soil was packed to 1.13, 1.32, 1.48, and 1.82 Mg kg(-1), resulting in cone resistances of 0.18, 0.43, 1.20, and 2.50 MPa. Cotton was cropped for 30 days. Lime was applied to raise base saturation to 40, 52, and 67%. The highest base saturation caused a decrease in phosphorus (P) and zinc (Zn) concentrations in the plants. A decrease in root dry matter, length and surface area was also observed. This could be a consequence of lime induced Zn deficiency. Root growth was decreased in the compacted layer, and complete inhibition was noticed at 2.50 MPa. Once the roots got through the compacted layer, there was a growth recovery in the bottom layer of the pots. The increase in base saturation up 52% was effective in preventing a decrease in cotton root length at soil resistances to 1.20 MPa. Where the roots were shorter, there was an increase in nutrient uptake per unit of root surface area, which kept the plants well nourished, except for P.